PENGEMBANGAN INSTRUMEN PENGUKUR KEDISIPLINAN KERJA PADA MITRA PERUSAHAAN LISTRIK DI SEMARANG - Catur Sihono (Media Bina Ilmiah, 2024)
Work discipline is an important factor that has a significant impact on performance and productivity in the workplace. Increasing employee work discipline has an impact on increasing company productivity because employees can be more obedient to company regulations in accordance with applicable regulations to be able to improve employee performance, where increasing employee productivity is influenced by increasing employee discipline so that they can be more obedient to existing regulations in a company. This research is development research which aims to determine the form of an instrument for measuring work discipline and determine the validity and reliability of tests in the field. The research subjects were 60 employees of PT Mitra Electricity Company with data collection techniques using interviews, observation, and distribution of questionnaires. The statements in this research are divided into 3 indicators, namely: 1) Attendance, 2) Compliance with work rules, 3) Compliance with work standards, the total number of statement data is 15 items, each indicator has 5 statement items and uses a Likert scale with the following conditions: 5 (strongly agree), 4 (disagree), 3 (disagree), 2 (disagree), 1 (strongly disagree). Based on the results of research on the validity and reliability test of the instrument measuring work discipline, there were 3 items that were invalid <0.3 and in the reliability test the value was more than 0.6 so it can be concluded that it is reliable and suitable for use in the field.